A blessing or a curse? Can digital economy development narrow carbon inequality in China? - Congyu Zhao; Jianda Wang; Kangyin Dong; Xiucheng Dong (Carbon Neutrality, 2023)
Abstract The importance of carbon emissions reduction notwithstanding, the issue of its inequality should also elicit the urgent attention of scholars. This paper first evaluates the carbon inequality between urban and rural areas based on a panel dataset of 30 provinces in China from 2006 to 2019. Then we quantitively investigate the role of digital economy development in reducing carbon inequality. We further explore the possible moderating role of residential disposable income in the rural areas and the impact channels in the nexus between digital economy development and carbon inequality. We find that (1) the relationship between digital economy development and carbon inequality is negative, and digital economy development exerts a significant mitigating impact on carbon inequality. (2) The nexus between digital economy development and carbon inequality is heterogeneous in terms of capital: provinces endowed with lower levels of social and human capital tend to exhibit a stronger connection between digital economy development and carbon inequality. (3) Rural residential disposable income can not only reduce carbon inequality, but can also show a synergistic effect with digital economy development, which means the interaction between rural residential disposable income and digital economy development also restricts carbon inequality significantly. (4) Digital economy development works on carbon inequality by increasing environmental regulation and technology innovation, and these two channels show a mitigating impact on carbon inequality. We propose several policy implications to accelerate the reduction of carbon inequality and the improvement of digital economy development.